Evaluation of Clinico-Demographic Profile and Survival Rate among Patients of Head and Neck Cancer - Anand Shah; Ravi Patel; Shashank Pandya; Jayesh Solanki; Vaishali Ravani (Medsci Publications, 2022)
Background: Head and Neck cancer (HNC) is a recognized major public health concern all over the world Objectives: To study age and gender predilection and clinical profile of Head & Neck Cancers Materials and Methods: This was a retrospective study including 21121 patients with Head & Neck Cancer presented to tertiary care centre, Ahmadabad. Patients' details of age, sex, site of carcinoma, stage at presentation and Outcome were recorded. The data was analyzed using MS office excel 2010 and Epi info software version 7.0. Result: Male to female ratio was 4.8:1. The most common site of presentation of tumour was in cheek mucosa (29.01 %). On comparison of different anatomical sites, majority of patients were presented in locally advanced stage. Significant association (p<0.05) was found between presentation of disease and literacy status. Overall 5 - year survival rate was 60.5% ± 1.6% when disease was localized. Conclusion: Majority of patients diagnosed in locally advanced stage. Strategies for the early diagnosis and prevention of Head & Neck cancer must be undertaken by government to overcome this situation.